Parallel vs. Convergent Evolution in Domestication and Diversification of Crops in the Americas - Pickersgill, Barbara (Frontiers in Ecology and Evolution, 2018)
Domestication involves changes in various traits of the phenotype in response to human selection. Diversification may accompany or follow domestication, and results in variants within the crop adapted to different uses by humans or different agronomic conditions. Similar domestication and diversification traits may be shared by closely related species (parallel evolution) or by distantly related species (convergent evolution). Many of these traits are produced by complex genetic networks or long biosynthetic pathways that are extensively conserved even in distantly related species. Similar phenotypic changes in different species may be controlled by homologous genes (parallel evolution at the genetic level) or non-homologous genes (convergent evolution at the genetic level). It has been suggested that parallel evolution may be more frequent among closely related species, or among diversification rather than domestication traits, or among traits produced by simple metabolic pathways. Crops domesticated in the Americas span a spectrum of genetic relatedness, have been domesticated for diverse purposes, and have responded to human selection by changes in many different traits, so provide examples of both parallel and convergent evolution at various levels. However, despite the current explosion in relevant information, data are still insufficient to provide quantitative or conclusive assessments of the relative roles of these two processes in domestication and diversification